2016
DOI: 10.1016/j.jhydrol.2015.12.061
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling inter-catchment variation of mean transit time with consideration of temporal variability

Abstract: 17The catchment transit time, a lumped descriptor reflecting both time scale and spatial structure of 18 catchment hydrology can provide useful insights into chemical/nuclear pollution risks within a catchment. 19Despite its importance, factors controlling spatial variation of mean transit time (MTT) are not yet well 20 understood. In this study, we estimated time-variant MTTs for about ten years (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) in five 212 / 42 mesoscale sub-catchments of the Fuj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Consequently, groundwater discharge does not have a discrete age but rather has a distribution of transit times. MTTs are commonly estimated using lumped parameter models (LPMs) that describe the distribution of water with different ages or tracer concentrations in simplified aquifer geometries (Maloszewski andZuber, 1982, 1996;Maloszewski et al, 1983;Cook and Bohlke, 2000;Maloszewski, 2000;Zuber et al, 2005). LPMs represent a viable and commonly used alternative to estimating MTTs using numerical groundwater models that rely upon hydraulic parameters that are seldom known with certainty and which vary spatially.…”
Section: Estimating Mean Transit Times (Mtts)mentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, groundwater discharge does not have a discrete age but rather has a distribution of transit times. MTTs are commonly estimated using lumped parameter models (LPMs) that describe the distribution of water with different ages or tracer concentrations in simplified aquifer geometries (Maloszewski andZuber, 1982, 1996;Maloszewski et al, 1983;Cook and Bohlke, 2000;Maloszewski, 2000;Zuber et al, 2005). LPMs represent a viable and commonly used alternative to estimating MTTs using numerical groundwater models that rely upon hydraulic parameters that are seldom known with certainty and which vary spatially.…”
Section: Estimating Mean Transit Times (Mtts)mentioning
confidence: 99%
“…Large groundwater storage volumes will likely also result in long MTTs (e.g. Ma and Yamanaka, 2016). Groundwater flow is likely to be more rapid through steeper catchments due to the higher hydraulic gradients, resulting in shorter MTTs (e.g.…”
Section: Predicting Mean Transit Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, this can help provide insights into potential impact of human activities on water partitioning in the landscape (Banks, Simmons, Love, & Shand, ). Previous studies have shown that controls on water ages are complex and can depend on the internal structure of the catchment and can be variously dominated by physiographical characteristics, including drainage density (Hrachowitz, Soulsby, Tetzlaff, Malcolm, & Schoups, ), topography (McGuire et al, ; Mosquera et al, ), soil cover (Hrachowitz et al, 2009), soil hydraulic properties (Heidbüchel, Troch, & Lyon, ; Muñoz‐Villers, Geissert, Holwerda, & McDonnell, ), land cover (Ma & Yamanaka, ), and their spatial variation. However, several of these characteristics can be affected by land management (e.g., Soulsby, Birkel, Geris, & Tetzlaff, ), which makes MTT a useful indicator to evaluate land use impacts on hydrological processes (Jacobs et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, rainfall–runoff processes have been analysed and examined by multiple researchers based on spatial‐ and component‐based information. However, unfortunately, there are few studies incorporating the timescale (age information) in the groundwater component, including the bedrock groundwater component of the rainfall–runoff water during rainstorms, even though the stream water age has been analysed in previous studies (e.g., Klaus et al, ; Ma & Yamanaka, ). The stable isotope‐based convolution integral methods have been known as traditional and effective dating methods of discharge water (reviewed in McGuire & McDonnell, ).…”
Section: Introductionmentioning
confidence: 99%